2002
DOI: 10.1088/1464-4258/4/6/380
|View full text |Cite
|
Sign up to set email alerts
|

A twofold modulation frequency laser range finder

Abstract: The purpose of this paper is to present the conception of a twofold modulation frequency laser range finder. The system is based on the phase-shift measurement method with two modulation frequencies, one giving the distance within a wide range and a second one leading to high resolution measurement. The measurement method is based on intermediate frequency sampling associating the under-sampling technique with digital synchronous detection. Its main advantage is a global simplification of the electronic system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…The technique adopted for the simultaneous collection of distance and color information is based on amplitude modulation [6][7][8] of three monochromatic laser sources (680 nm, 532 nm, and 460 nm), which operate as carrier waves. The distance and color information are extracted from modulating waves by phase-shift and reflectivity responses of the target at the three wavelengths.…”
Section: Methodsmentioning
confidence: 99%
“…The technique adopted for the simultaneous collection of distance and color information is based on amplitude modulation [6][7][8] of three monochromatic laser sources (680 nm, 532 nm, and 460 nm), which operate as carrier waves. The distance and color information are extracted from modulating waves by phase-shift and reflectivity responses of the target at the three wavelengths.…”
Section: Methodsmentioning
confidence: 99%
“…An interesting approach is described in [23], where the phase-based method, implementing a double frequency modulation, is applied for wide-range and high-resolution ranging using undersampling. The pulse-based technique is suitable for long range applications, allowing safe high-power emissions due to the short duration of the pulses.…”
Section: Contextmentioning
confidence: 99%
“…Generally an extension of the nonambiguity range can be achieved by using two different modulation frequencies analog to the multiple wavelength interferometry technique [24]. In [25] it was shown that no additional phase-shift measurement stages are necessary in order to process a twofold modulation frequency for an increase of the nonambiguity range.…”
Section: Signal Processingmentioning
confidence: 99%